2019
DOI: 10.22502/jlmc.v7i1.272
|View full text |Cite
|
Sign up to set email alerts
|

Hand Index- A Forensic Tool for Sexual Dimorphism

Abstract: Introduction:Amongst the various parameters of identification, sex is one of the most important elements. Figuring out hand index from measurement of hand dimensions is a convenient way to determine sexual dimorphism. This study aims to find out sexual dimorphism from hand dimensions, obtain cut off points for male and female and check percentage accuracy of sex determination from hand dimensions in Nepalese population. Methods: The data was collected from 400 asymptomatic, healthy working staff (229 males and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…The average hand index in males was 47.73 whereas the female hand index was 45.46 (Table 2). Several research investigations have been carried out on sex determination from hand dimensions (HL and HB) and also suggest the findings that males have significantly larger hand dimensions than the females counterparts (Aboul-Hagag et al 2011;Rani et al 2011;Sen et al 2011;Asha et al 2012;Ibrahim et al 2016;Varu et al 2016;Caplova et al 2017;Gupta et al 2017;Singh and Yadav 2017;Sah and Jeelani 2019). Results of the present investigation showed sex-specific mean differences in HL and HB (p<0.05) (Table 3).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The average hand index in males was 47.73 whereas the female hand index was 45.46 (Table 2). Several research investigations have been carried out on sex determination from hand dimensions (HL and HB) and also suggest the findings that males have significantly larger hand dimensions than the females counterparts (Aboul-Hagag et al 2011;Rani et al 2011;Sen et al 2011;Asha et al 2012;Ibrahim et al 2016;Varu et al 2016;Caplova et al 2017;Gupta et al 2017;Singh and Yadav 2017;Sah and Jeelani 2019). Results of the present investigation showed sex-specific mean differences in HL and HB (p<0.05) (Table 3).…”
Section: Discussionsupporting
confidence: 78%
“…The individual hand, when recovered and brought for forensic examination, can provide valuable information about the age, sex and stature of the person (Robling and Ubelaker 1997;Sen et al 2014;Jeanson et al 2017;Adelakun et al 2019;Singh et al 2019a,b). There are several research investigations, which have been undertaken to establish the relation between sex and hand dimensions in terms of HL and HB in adults (Sen et al 2011;Asha et al 2012;Uhrova et al 2015;Ibrahim et al 2016;Varu et al 2016;Caplova et al 2017;Gupta et al 2017;Singh and Yadav 2017;Sah and Jeelani 2019). The results of the present investigation showed that the male hands are significantly larger compared to the female counterparts thus showing sexual dimorphism on the basis of hand length (HL) (p<0.05) (Table 1).…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…The problem arises when the body parts found are in a fragmented or mutilated state in mass disasters, accidents, explosions and crime scenes (Agnihotri et al 2005;Rani et al 2011;Uhrová et al 2015;Pal et al 2016;Bindurani et al 2017). Sometimes a forensic anthropologist works with skeletonised or badly decomposed body segments and collect osteometric data, which is generally straight forward in population (Sarode et al 2009; García-J Life Science, 12(1-2): 1-11 (2020) Parra et al 2014;Jee et al 2015;Curate et al 2017;Monum et al 2017;Ubelaker and DeGaglia 2017;Sah and Jeelani 2019).…”
Section: Introductionmentioning
confidence: 99%